Does R&D spur productivity growth in Australia’s broadacre agriculture? A semi-parametric smooth coefficient approach - Khan, F.; Salim, Ruhul; Sun, K. (Routledge, 2018)
© 2018 Informa UK Limited, trading as Taylor & Francis Group This article analyses the role of research and development (R & D) in Australia’s broadacre farming by using the semi-parametric smooth coefficient model. While the conventional production function approach only captures the direct effects of R & D, this methodology captures both the direct impact of a change in R & D on output and the indirect impact through changes in efficiency of use of factor inputs in the production process. Moreover, technical inefficiency is introduced in the model allowing it as a function of R & D. Using a unique state-level dataset covering the period 1995–2007, this empirical study finds that once both the direct and indirect effects are taken into consideration, R & D investments significantly increase outputs. The results also show that there are substantial variations in the effects of R & D on output across the state-level average farm through technology parameters as well as through technical inefficiency. Such variations need to be taken into account when designing policies for investing public R & D in agriculture.